Multi-Area QoS Provisioning Using Hierarchical Bandwidth Brokers Architecture - Chaw, Ling Teck; Keat Keong, Phang; Fong, Ang Tan; Pei, Lim Gek (Malaysian Journal of Computer Science, 2008)
In this paper, an intra-domain, multi-area Quality of Service (QoS) provisioning mechanism, namely the QoS-HBB architecture is proposed to alleviate the scalability problem in the intra-domain bandwidth broker design. By exploiting the inherent hierarchical nature of OSPF and the fact that an OSPF domain can be subdivided into multiple areas, QoS-HBB introduces two levels (i.e. intra-area and inter-area) of QoS provisioning within a domain. The proposed architecture allows the deployment of multiple bandwidth brokers in the backbone area and non-backbone areas. At the intra-area level, a child bandwidth broker is deployed in every non-backbone area to handle intra-area QoS provisioning; whereas, at the inter-area level, QoS control functions are delegated from the child bandwidth broker to the parent bandwidth broker situated at the backbone area. With the hierarchical design and efficient QoS state information maintenance, QoS-HBB is capable of providing service assurance to end-user applications. Furthermore, Multi-Protocol Label Switching (MPLS) and path caching are incorporated to improve the performance. Simulation results show that, compared to ordinary OSPF, QoS-HBB significantly improves QoS provisioning in terms of packet loss ratio, link utilization, end-to-end delay, packet commit percentage, and throughput.